The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1361-6528/ab9869
|View full text |Cite
|
Sign up to set email alerts
|

Defect studies on short-wave infrared photovoltaic devices based on HgTe nanocrystals/TiO2 heterojunction

Abstract: Narrow bandgap (<0.5 eV) colloidal semiconductor nanocrystals (e.g. mercury chalcogenides) provide practical platforms for next generation short wave infrared, mid wave infrared and long wave infrared optoelectronic devices. Until now, most of the efforts in the field of infrared active nanocrystals have been taken on synthesizing nanocrystals, determining quantum states and building different geometries for optoelectronic devices. However, studies on interface trap states in the devices made from these narrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Various 0D materials, such as CsPbBr 3 quantum dots, HgTe nanocrystals, and PbS quantum dots, were hybridized with low-dimensional metal oxides to modulate the surface/interface charge behavior and optimize the photodetector performance. Due to the intriguing interfacial charge transfer behavior, the mixed dimensional heterojunction has shown fascinating properties beyond the individual metal oxides. The decoration of 0D materials also changes the condition of the exposed material surface, thereby influencing the interaction of the photocarriers with chemisorbed foreign atoms or molecules. , Nitrogen-doped graphene quantum dots (NGQDs), an attractive carbon material, have extraordinary optical and electrical characteristics due to their pronounced quantum confinement and edge effects. The electron-rich nitrogen atoms endow NQGDs with extensive delocalized electrons and high charge carrier density, making them more favorable for potential optoelectronic devices. NGQDs have been reported to exhibit superior electron transfer/reservoir properties when incorporated into metal oxides, resulting in the high sensing performance of the hybrid structure. Moreover, compared with 0D materials mentioned above, NGQDs have the advantages of low toxicity, high chemical stability, and low cost .…”
Section: Introductionmentioning
confidence: 99%
“…Various 0D materials, such as CsPbBr 3 quantum dots, HgTe nanocrystals, and PbS quantum dots, were hybridized with low-dimensional metal oxides to modulate the surface/interface charge behavior and optimize the photodetector performance. Due to the intriguing interfacial charge transfer behavior, the mixed dimensional heterojunction has shown fascinating properties beyond the individual metal oxides. The decoration of 0D materials also changes the condition of the exposed material surface, thereby influencing the interaction of the photocarriers with chemisorbed foreign atoms or molecules. , Nitrogen-doped graphene quantum dots (NGQDs), an attractive carbon material, have extraordinary optical and electrical characteristics due to their pronounced quantum confinement and edge effects. The electron-rich nitrogen atoms endow NQGDs with extensive delocalized electrons and high charge carrier density, making them more favorable for potential optoelectronic devices. NGQDs have been reported to exhibit superior electron transfer/reservoir properties when incorporated into metal oxides, resulting in the high sensing performance of the hybrid structure. Moreover, compared with 0D materials mentioned above, NGQDs have the advantages of low toxicity, high chemical stability, and low cost .…”
Section: Introductionmentioning
confidence: 99%
“…This process could be repeated over multiple cycles to reach a thick enough and contiguous conductive QD film. 1,2-Ethanedithiol (EDT) is a firm favourite choice as a short bifunctional ligand to be adopted for the ligand substitution of a series of spin/cast deposited films of Hg chalcogenide QDs, 10,68,75,79,[87][88][89][90][91] and for the HgTe/CdSe core-shell nanoplatelet (NPL) thin films. 92 The process should be done in a dry N 2 gas environment in a glove-box as the dithiol crosslinked film is sensitive to air and moisture exposure.…”
Section: Ligand Exchangementioning
confidence: 99%
“…Kolkovsky et al also demonstrated deep-level defects in a GaN NR ensemble using the DLTS technique [7]. Recently, the DLTS technique has been used to identify the deep traps in photodetector (PD) devices [8]. The trap states in the semiconductor mid-gap region restrict the photogenerated electrons from reaching the conduction band, so the photocurrent generation is inhibited in the device.…”
Section: Introductionmentioning
confidence: 99%